2014
DOI: 10.1007/s00423-014-1223-5
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous union of the pancreaticobiliary duct without choledochal cyst: is cholecystectomy alone sufficient?

Abstract: Since cancers of the biliary tract occur more frequently in the AUPBD group without choledochal cyst,cholecystectomy alone may not be protective of the future occurrence of bile duct cancers, and thus, vigilant surveillance is necessary in this population group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…The prevalence of malignancy was 7·3 per cent among patients with choledochal malformation and the rate of malignant transformation was 3·4 per cent. This finding implies that treating choledochal malformation may reduce the risk of developing malignancy, and is consistent with the commonly accepted theory that carcinogenesis might be related to dysplasia and metaplasia of the epithelium of the choledochal malformation. Complete cyst excision followed by construction of a bilioenteric anastomosis is therefore believed to protect the patient from developing malignancy.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The prevalence of malignancy was 7·3 per cent among patients with choledochal malformation and the rate of malignant transformation was 3·4 per cent. This finding implies that treating choledochal malformation may reduce the risk of developing malignancy, and is consistent with the commonly accepted theory that carcinogenesis might be related to dysplasia and metaplasia of the epithelium of the choledochal malformation. Complete cyst excision followed by construction of a bilioenteric anastomosis is therefore believed to protect the patient from developing malignancy.…”
Section: Discussionsupporting
confidence: 86%
“…It could be speculated that prolonged reflux of pancreatic secretions into the biliary tract occurs in Todani types I and IV, which frequently present with abnormal pancreaticobiliary duct junctions. Prolonged reflux might lead to malignant degeneration of the biliary epithelium. The situation is supposedly different in types II and III choledochal malformations, which might be true congenital malformations in which reflux is absent.…”
Section: Introductionmentioning
confidence: 99%
“…Some investigators recommended removal of the extrahepatic bile duct along with the gallbladder to prevent cancer development in the remnant nondilated bile duct. 3 , 16 According to a study by Kim et al, 10 of 55 patients with AUPBD, conducted to evaluate the occurrence of biliary tract cancer, ECC occurred more frequently in patients without bile duct dilatation than in those with bile duct dilatation (30.0% vs 4.0%; P = 0.015). They recommended extrahepatic bile duct excision, biloenteric anastomosis, and cholecystectomy as a treatment of choice for AUPBD without bile duct dilatation; however, routine excision of the extrahepatic bile duct in AUPBD patients presents the risk of postoperative adverse events in 9.7% to 20% of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…Although controversy remains regarding the mechanism of carcinogenesis, many studies demonstrated that biliary tract cancers develop preferentially at sites where there is stasis of activated pancreatic enzymes, such as in the dilated bile duct or gallbladder. 10 In this regard, prophylactic flow-diversion surgery consisting of extrahepatic bile duct resection along with cholecystectomy is widely accepted as the treatment of choice for AUPBD patients with bile duct dilatation to prevent development of both bile duct and gallbladder cancer. 11 For AUPBD without bile duct dilatation, prophylactic cholecystectomy alone is generally performed and advocated in many institutions owing to the concept that the stasis of pancreatic enzymes occurs mainly in the gallbladder 5 ; however, some experts suggest excision of the extrahepatic biliary tract and cholecystectomy in AUPBD patients without biliary dilatation because reflux of pancreatic enzyme would still occur after cholecystectomy, thereby predisposing the patient to other biliary tract cancers.…”
Section: Introductionmentioning
confidence: 99%
“…For the rarest CM subtypes -common bile duct diverticula and choledochocele -with a low risk for malignant transformation, simple surgical excision or endoscopic discision are considered adequate approaches (11,14). Whether an isolated PBM without proximal dilatation warrants removal of the extrahepatic biliary tree or could be managed by cholecystectomy alone to decrease the risk for subsequent gallbladder cancer remains controversial (15,16).…”
mentioning
confidence: 99%